2020
DOI: 10.5653/cerm.2020.03489
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dual progesterone administration (intramuscular and vaginal) for luteal support in fresh day 3 or day 4 embryo transfer cycles

Abstract: Objective: The aim of this study was to compare in vitro fertilization outcomes between fresh day 3 or day 4 embryo transfer cycles with dual progesterone (P) administration (intramuscular and vaginal) and cycles with single intramuscular P administration for luteal support.Methods: We selected 124 cycles from 100 women (under age 40 years) who underwent oocyte pick-up (number of trials ≤ 3, 4–14 oocytes obtained) and transfer of two or three day 3 or day 4 embryos at two infertility centers from January 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Likewise, two recently published retrospective studies compared combined IM and vaginal progesterone vs. either IM or vaginal progesterone only LPS. Both studies showed similar outcomes for all study arms (7,8). Similarly, no significant differences were found between low-dose vs. high dose vaginal agents, short vs. long protocol, micronized vs. synthetic formulation or other administration forms (vaginal ring, gel) (3).…”
Section: Progesterone Routes Of Administration In Fresh Embryo Transfersmentioning
confidence: 91%
“…Likewise, two recently published retrospective studies compared combined IM and vaginal progesterone vs. either IM or vaginal progesterone only LPS. Both studies showed similar outcomes for all study arms (7,8). Similarly, no significant differences were found between low-dose vs. high dose vaginal agents, short vs. long protocol, micronized vs. synthetic formulation or other administration forms (vaginal ring, gel) (3).…”
Section: Progesterone Routes Of Administration In Fresh Embryo Transfersmentioning
confidence: 91%